Current theoretical models fail to predict the topological complexity of the human genome - Arsuaga, Javier; Jayasinghe, Reyka G.; Scharein, Robert G.; Segal, Mark R.; Stolz, Robert; Vazquez, Mariel (Frontiers in Molecular Biosciences, 2015)
Understanding the folding of the human genome is a key challenge of modern structural biology. The emergence of chromatin conformation capture assays ({\it e.g.} Hi-C) has revolutionized chromosome biology and provided new insights into the three dimensional structure of the genome. The experimental data are highly complex and need to be analyzed with quantitative tools. It has been argued that the data obtained from Hi-C assays are consistent with a fractal organization of the genome. A key characteristic \textcolor{red}{of the fractal globule} is the lack of topological complexity (knotting or inter-linking). However, the absence of topological complexity contradicts results from polymer physics showing that the entanglement of long linear polymers in a confined volume increases rapidly with the length and with decreasing volume. \textcolor{red}{{\it In vivo} and {\it in vitro} assays support this claim in some biological systems. We simulate knotted lattice polygons confined inside a sphere and demonstrate that their contact frequencies agree with the human Hi-C data.} We conclude that the topological complexity of the human genome cannot be inferred from current Hi-C data.